Text and Image Encryption Using Symmetric Cryptography Ron Rivest Cipher 2 (RC2) - Pratiwi, Saniya Rahma; Sari, Christy Atika; Rachmawanto, Eko Hari (Politeknik Ganesha Medan, 2024)
In the current context, ensuring the secure transmission of data over the internet has become a critical concern, with information technology playing a fundamental role. As society advances into the digital information age, the importance of network security issues continues to increase. Therefore, the need for cryptographic technology has emerged to overcome these challenges. Cryptography includes symmetric and asymmetric cryptography. An example of symmetric cryptography is the RC2 algorithm. RC2 is a symmetric encryption algorithm that uses a single key to encrypt and decrypt data. The ciphertext is then concealed within an image using the Stepic technique. The RC2 encryption method also utilizes symmetric encryption, ensuring the security of the encryption process while maintaining efficient encryption and decryption speeds. The result of this research is that the average percentage of MSE is 0.00%, and for PSNR and AVA are 70.85% and 34.93%. However, the AVA value is quite unstable because the average value is below 40%. Meanwhile, image encryption results in the longer the text that needs to be hidden in the image, the higher the UACI percentage. This is inversely proportional to the NPCR, the longer the text that needs to be hidden in the image, the lower the NPCR percentage. The average results obtained for UACI and NPCR values are 41.46% dan 98.13%.